Evaluation of targeted and immune combination therapies in a rat model of hormone receptor–positive breast cancer - Ernesto Rojas-Jimenez; Triet M. Bui; Pengze Yan; Zheqi Li; Marco Seehawer; Jun Nishida; Pierre Foidart; Gordon J. Freeman; Kornelia Polyak (Proceedings of the National Academy of Sciences, 2026)
Estrogen receptor (ER) positive breast cancer is the most prevalent subtype, commonly responsive to endocrine therapies. Immune checkpoint inhibitors (ICIs) have limited efficacy in ER-positive disease, highlighting the need for the development of combination immunotherapies for these patients. We previously established that nitroso-N-methylurea-induced mammary tumors in outbred Sprague-Dawley rats mimic immune evasive mechanisms and the heterogeneity of ICI response observed in patients. We identified a “luminal growing” gene signature in ER-positive tumors, which correlated with tumor growth and immune-related differences. Here, we evaluated targeting candidates from this signature KMT5B/C and IKBKE using inhibitors A-196 and IKBKEi respectively, alongside anti-estrogen (fulvestrant) and a TGFβ blocking antibody (NIS793), both individually and in combination with αPD-L1, within this rat model. Fulvestrant emerged as the most effective treatment, inducing regression of most existing tumors and reducing on-treatment tumor burden when combined with αPD-L1. A-196, while ineffective as a monotherapy, demonstrated enhanced response when combined with αPD-L1. Comprehensive tumor profiling through polychromatic flow cytometry and single-cell RNA sequencing revealed that A-196 induced a luminal-to-basal shift in tumor epithelial cells, enhancing antigen presentation, whereas epithelial-to-mesenchymal transition was linked to fulvestrant resistance. Our findings underscore the value of the rat mammary tumor model for preclinical studies in ER-positive breast cancer and advocate for the further validation and potential clinical development of KMT5B/C inhibitors to enhance the efficacy and broaden the applicability of ICI therapy in cancer patients.